Extradural anaesthesia-analgesia in dogs undergoing cholecystectomy: A single centre retrospective study - Sambugaro, Beatrice; De Gennaro, Chiara; Hattersley, Rachel D.; Vettorato, Enzo (Frontiers in Veterinary Science, 2022)
Objectives To assess the effects of extradural anaesthesia-analgesia (EAA) in dogs undergoing cholecystectomy. Materials and methods Medical records of dogs undergoing cholecystectomy between 2011 and 2019 were retrieved and allocated to two groups depending if analgesia was provided systemically (group SA) or extradurally (EAA). Preoperative data, intraoperative antinociceptive medications, postoperative analgesia, perioperative complications, and food intake were compared. Results Overall 41 medical records were included in the study: 19 and 22 dogs were allocated to groups SA and EAA, respectively. In group EAA, an extradural catheter was placed preoperatively in 8 dogs; in the remaining, it was placed postoperatively but an extradural injection was performed preoperatively. The extradural catheter tip was between the 4th lumbar and the 10th thoracic vertebrae. Intraoperatively, nociception was more likely to occur in group SA [OR 55.42 (2.97–1,035.06)]. During the first 24 and 48 h postoperatively, more dogs in group SA required methadone [OR 24 (2.81–268.4) and OR 11.56 (2.37–45.06), respectively] and additional analgesic drugs [OR 25 (3.47–281.9) and OR 35.29 (1.86–668.2), respectively] compared to group EAA. Voluntary postoperative food intake was also significantly higher in group EAA. Clinical significance Compared to systemic analgesia, the use of extradural anaesthesia-analgesia reduced perioperative analgesic requirement and promoted postoperative food intake in dogs undergoing cholecystectomy.